ESTUDIO MONOGRAFICO DE LAS PSYCHIDAE DE MEXICO I - VAZQUEZ, G LEONILA (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
The larva of A suffumosa is descr It imbeds itself head downward in the middle of the flower of Cosmos bipinnatus
ANS INST BIOL
Keywords: ESTUDIO MONOGRAFICO, PSYCHIDAE, MEXICO I; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; INSECTOS